Brachial Artery Thrombosis following Multiple Wasp Bites - K. U. I. S. Gunathilake; M. I. M. Rifath; D. D. Ayeshmantha; J. K. K. N. Jayasinghe; A. Marasinghe (Case Reports in Medicine)
Wasp bites can give rise to multiple clinical manifestations ranging from local reactions to multisystem involvement. Stroke and myocardial infarctions following wasp envenomation are reported in the literature. We describe a rare case of brachial artery thrombosis following multiple wasp bites.